hp-HGS strategy for inverse AC/DC resistivity logging measurement simulations - Gajda-Zagorska, Ewa; Paszynski, Maciej; Schaefer, Robert; Pardo, David (Computer Science, 2013)
In this paper we present resistivity logging measurement simulation with the usage of two types of borehole logging devices: operating with zero frequency (direct current, DC) and those operating with higher frequencies (alternate current, AC). We perform simulations of 3D resistivity measurements in deviated wells, with the sharp angle between the borehole and formation layers. We introduce hierarchical adaptive genetic strategy $hp-HGS$ interfaced with adaptive finite element method. We apply the strategy for the solution of the inverse problem, where we identify the resistivities of the formation layers based on a given measurement. We test the strategy on both direct and accurate currect cases.